DETERMINAN EKSPOR TEH INDONESIA - I Made Oka Wirajaya; Anak Agung Bagus Putu Widanta (Jurnal Ekonomi dan Bisnis, 2024)
The volume of exports generated in Indonesia by the non-oil and gas sector is higher than the value of exports generated by the oil and gas sector. The plantation sector is one of the important sectors in the Indonesian economy. This is supported by the vast territory and tropical climate of Indonesia. One of the leading products in the plantation sector in Indonesia in export activities and the domestic market is the tea commodity. This study aims to analyze the effect of production variables, USD exchange rate, land area, and domestic market simultaneously and partially on the volume of Indonesian tea exports in 2009- 2021. The analysis technique used is multiple linear regression analysis. The results of data analysis show that: 1) production, USD exchange rate, land area, and domestic market simultaneously have a significant effect on the volume of Indonesian tea exports in 2009-2021. 2) production partially has a positive and significant effect on the volume of Indonesian tea exports. 3) the USD exchange rate partially has no positive and insignificant effect on the volume of Indonesian tea exports. 4) land area partially has a positive and significant effect on the volume of Indonesian tea exports. 5) domestic market partially has no positive and significant effect on the volume of Indonesian tea exports. Given the importance of exports for a country's economy, the export of tea commodities, which is one of Indonesia's leading export commodities, must be increased, taking into account factors that can affect the value of exports.